ALUMINIUM CANS WASTE MELTING IN MICROWAVE FIELD - PASCARIU, Alexandra Gabriela; ANASIEI, Ioana; DUMITRESCU, Daniela Violeta; BURADA, Marian; OLARU, Mihai Tudor; ŞERBAN, Beatrice Adriana; COVIC, Paul; COSMULESCU, Felicia; ŞCHIOPU, Ciprian; CÎMPAN, Tiberiu (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
Recycling of aluminium, particularly aluminium beverage cans is important due to several economic and environmental reasons. Aluminium beverage cans are by far the most recycled consumer beverage packages globally, by units, weight and percentage recycled. It amounts to more than twice the recycling rate and recycled content percentages for beverage packages of other materials. Recycling of aluminium requires only 5-10% of the energy for primary aluminium production. In this paper, the melting of cans wastes in microwave furnace as well as the treatment of noxious emissions in a microwave thermal filter has been preliminary investigated. Melting temperature, composition of the melting - protection fluxes as well as waste/flux ratio on the metal recovery efficiency have been investigated. During the cans waste melting, due to the burning of paint and lacquer coatings, environmental toxic compounds such as: volatile organic compounds (VOCs) (acetone, benzene, ethylbenzene, styrene, toluene, etc.) have been detected in the effluent gases. The treatment was carried out by passing the gases through a microwave susceptor granular material filter (SiC balls), placed in a microwave transparent tube. It was observed that the temperature of the filter has a major influence on the neutralization of the toxic compounds, the content in the gases being reduced below the legal limits.